Perubahan Panjang Badan, Tinggi Pinggul Dan Tinggi Pundak Kambing Kacang Jantan Yang Mengalami Tingkat Pembatasan Pakan Yang Berbeda - Nahak, Gregorius Renerius; Tahuk, Paulus Klau; Bira, Gerson Frans (Bantara Journal of Animal Science, 2023)
This study aims to determine the increase in body length, hip height and shoulder height of Kacang goat at different levels of food restriction. The research was carried out in the goat pen of the Agriculture Faculty, Timor University from June until September 2022. The cattle used were 15 male Kacang goats with an average body weight of 10-15 kilograms (kg). This study used a Completely Randomized Design (CRD) experiment methode consisting of 3 treatments and 5 replications. The treatments used in this study were: T0 = Cattle without being restricted by feed, T1 = Cattle being limited by feed (100%) of maintenance life, T2 = Cattle being limited by feed (50%) of maintenance life. The variables observed in this study were body length, hip height and shoulder height. The data analyzed by using Analysis of Variance (Anova) and Duncan's multiple range test. The results showed that the average change in body length of male Kacang goat in the T0, T1, and T2 treatments was 0.040; -0.050; and -0.060 cm/head/day, respectively. Shoulder height of 0.060; -0.080; and -0.083 cm/head/day, respectively. Hip height of 0.087; -0.090; and -0.10 cm/head/day, respectively. Statistical analysis showed that the treatment had a significant effect on body length, shoulder height and hip height of male kacang goats (P<0.05). It was concluded that the T0 treatment without being restricted by feed gave the best results on changes in body length, shoulder height, and hip height in male Kacang goat.